Un trébol de cuatro hojas. Las Juventudes Comunistas de Chile en el siglo XX - Loyola, Manuel (Ariadna Ediciones, 2014)
Set dedicated to the Young Communists, youth organization of Chilean communism. Aspects of their culture, organization, political action, militancy are reviewed